Interpretasi Elemen Visual Poster Film "Exit" : Kajian Semiotik Saussure - Fadhil Mahesa Ali; Tiara Lie Kamilatin; Ervina Suhendar; Muhammad Chairil Abdul Aziz; Fatimah Nur Khilafah; Mujahidah Afifah; Tazkia Riska Alviana Azhari; Oryza Sativa; Febriansyah Febriansyah (Filosofi : Publikasi Ilmu Komunikasi, Desain, Seni Budaya, 2024)
A film poster functions as a visual communication tool that has an influence on the initial perception of the audience. The elements contained in the poster help the audience understand the message conveyed through a film. This research analyses the movie poster “Exit” using Ferdinand de Saussure's semiotic approach, which divides the sign into two parts, namely signifier and signified. The method used in this research is descriptive qualitative, where this research uses data sources consisting of secondary data and primary data. The researcher describes the elements of the poster in detail, both visual appearance and verbal text, then conducts interpretative analysis. The data obtained were grouped based on the meaning of visual signs, verbal signs, and image signs in the film poster. The results show that the film poster ‘Exit’ is effective in utilising visual elements to provide a clear initial description of the film's theme and attract the audience's attention. The dynamic incorporation of visual elements and the appropriate use of text on this poster successfully communicate the genre, theme, and atmosphere of the film. Thus, this poster not only functions as a promotional tool but also as a medium that shapes the audience's perception of the film.